Another Decomposition of Continuity via gμ-closed Sets - Selvaraj Ganesan; Sakkari Veeranan Chandrasekar (International Journal of Mathematics And its Applications, 2016)
There are various types of generalization of continuous functions in the development of topology. Recently some decompositions of continuity are obtained by various authors with the help of generalized continuous functions in topological spaces. In this paper we obtain a decomposition of continuity using a generalized continuity called gμ-continuity in topology.